Development of protocols for genomic library construction of Agarwood (Aquilaria malaccensis) - ULFAH J. SIREGAR; MUHAMMAD IQBAL MAULANA; UTUT W. SUHARSONO (Society for Indonesian Biodiversity, 2017)
Siregar UJ, Maulana MI, Suharsono UW. 2017. Development of protocols for genomic library construction of Agarwood (Aquilaria malaccensis). Biodiversitas 18: 1150-1158. Agarwood is one of non timber forest products (NTFP) which has high economic value. Diminishing agarwood trees in natural forest due to intensive harvesting has shifted the production paradigm to forest plantation. In order to support agarwood tree improvement, investigation on the agarwood tree genomes and genes involved in agarwood production is highly needed through genomic library construction. This research aimed at establishing cloning protocols for genomic library construction of agarwood tree (Aquilaria malaccensis) until sequencing process. Genomic DNA was isolated using DNeasy Plant Mini Kit from Qiagen, then was digested with EcoR1, and was ligated to pGemÂ®-T Easy vector system before it was finally transformed and was cloned to E.coli strain DH5Î±. Confirmation of DNA inserts was done using PCR colony with universal primer of SP6 and T7, plasmid isolation and also PCR plasmid and plasmid DNA digestion used Quick Plasmid Miniprep Kit from Thermofisher. Cloned A. malaccensis DNA fragments were sequenced and BLAST at NCBI site. The cloning successfully obtained five white colonies which contain inserted A. malaccensis DNA fragments with the size of 136-225 bp. PCR colony, plasmid isolation, PCR plasmid, and plasmid DNA digestion had confirmed the existence of inserted A. malaccensis DNA genome inside the bacteria cells. Sequencing and BLAST showed that DNA inserts from colony number 6, 8, and 9 were not similar with A. malccensis sequence that was recorded in NCBI, indicating that the genomic region in this library construction is different from the genomic DNA sequences of A. malaccensis in NCBI.